Effective light management, stretchable and transparent nanofiber electrode via the incorporation of phosphors into composite nanofibers for wearable perovskite solar cells. Issue 13 (July 2023) - Cao, Yimin; Zhang, Wenjie; Shi, Fanglin; Chen, Tianying; Du, Pingfan; Song, Lixin; Xiong, Jie
The flexible transparent electrode is a crucial component of wearable photoelectric devices, and has a significant influence on the performance and development of wearable devices. Here, a phosphor/polyimide/polyurethane@silver composite nanofiber (NF) web electrode was fabricated by electrospinning and magnetron sputtering for wearable photoelectric devices. The electrode demonstrated a promising light management ability with converting ultraviolet light to visible light, high conductivity with sheet resistance of 22.1 Ω/square, and high transparency with transmittance of over 80%. Besides, the electrode possessed an excellent stretched capacity with tensile strain of over 100%, and tensile stability with the resistance increased by ∼75% after 500 stretching cycles at the tensile stain of 50%. As a result, a flexible perovskite solar cell (PSC) was assembled by using the NF web electrode, and possessed the power conversion efficiency of 3.47%, which is higher than that of PSCs based on electrodes without phosphor. Furthermore, the flexible PSCs exhibited promising mechanical stability under bending, and could serve as wearable devices. This work provides a feasible and promising method to prepare lightweight, stretchable, light management, and transparent electrodes for photoelectric devices, and may facilitate the development of wearable photoelectric devices.